The peat swamp:Productivity, traficability and mechanization - Rahman, Mohammed Ataur; Rafia, Afroz; Yahya, Azmi (Nova Science Publishers Inc., 2012)
The Peat Swamp: Productivity, Traficability and Mechanization has been written with emphasizing the fundamental engineering principles underlying the peat characteristics, importance of peat,peat environmental affect, determination of the mechanical properties of peat terrain, mechanization of peat based on the vehicle for highland, moderate peatland and worst or peat swamp . The mechanization of peat has been discussed with the way to the development of peat vehicle and their performance. Specially, intelligent vehicle development discussion is one of the cores of this book. This book is intended to introduce senior undergraduate and postgraduate students to study on the peat terrain and theory of peat vehicle mobility. The green house gas (GHG) emission from the peat which is mainly incurred due to the aggressive agricultural planned implemented on the peat is discussed. An analytical framework for determining the mechanical properties of peat in view of predicting the tractive performance of vehicle is presented. The measuring techniques of the stiffness of peat’s surface mat and underlying weak peat are also presented. An intelligent control system is presented in this book with air-cushion tracked vehicle which is more enhancing the vehicle mobility over the swamp terrain. The intelligent advanced hybrid air-cushion tracked vehicle for peat swamp is presented in this book which is developed with incorporating the depth knowledge of terramechanics and different discipline of engineering to make this book more attractive to the automotive professional.